Efektifitas Penerapan Job Desk Dinas Lingkungan Hidup Bidang Pengendalian Pencemaran dan Kerusakan Lingkungan Hidup (PPKL) - Lubis, Suci Arifah; Mahira, Tengku Ismalia; Lestari Nasution, Annio Indah (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This research uses a qualitative descriptive research type. In determining this information the researcher used data collection techniques using in-depth interviews, observation, documentation and data collection. Job description is the most important thing in an organization because it really determines the running of the organization's wheels, obstacles and benefits in the organization can be determined from an analysis. This study aims to determine the effectiveness of the application of job descriptions in DLH-SU, especially in the field of PPKL